Reflections on intervention strategies with respect to the process of alcoholization and self-care practices among Kaingang indigenous people in Santa Catarina State, Brazil - Ari Ghiggi Junior; Esther Jean Langdon (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
This article, based on ethnographic research on the Xapecó Indigenous Reservation in Santa Catarina State, Brazil, examines the sociocultural context of the use of alcoholic beverages among the Kaingang indigenous people. The authors also discuss the experience with an intervention involving government agencies and nongovernmental organizations that attempted to deal with alcohol-related problems on the reserve. Based on the concepts of alcoholization and self-care practices, the study analyzes the possibilities for organizing health intervention practices with indigenous peoples, in light of the principle of differentiated care under Brazil's National Healthcare Policy for Indigenous Peoples.